INTERNALISASI AKHLAK HORMAT KEPADA ORANG TUA MELALUI KONTEN YOUTUBE ISLAMI - Illyin Salsa; Agnes Monica; Roudlotul Jannah; Berliana Ramadhani Hasibuan; Ep Riadi; Rangga Apri Sandi; Ibnu Rozali (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
The development of digital technology has significantly transformed the process of moral education among young generations, particularly through the use of YouTube as a medium for learning and Islamic preaching. Islamic YouTube content is considered capable of supporting the internalization of moral values, especially respect for parents (birrul walidain), through engaging, communicative, and easily understood moral messages for adolescents. This study aims to analyze the role of Islamic YouTube content in instilling the values of respect toward parents and to examine the supporting and inhibiting factors in the process of moral internalization in the digital era. The research employed a qualitative library research method through the analysis of various relevant journals, books, and scientific articles. The findings show that Islamic content such as religious lectures, educational animations, exemplary stories, and motivational videos can help develop adolescents’ moral awareness. However, the effectiveness of moral internalization is still influenced by content quality, digital literacy, family environment, and parental supervision in the use of social media.